The addition of hyaluronic acid in chemical hydrogels can tune the physical properties and degradability. (5th December 2021) - Pizzetti, Fabio; Maspes, Anna; Rossetti, Arianna; Rossi, Filippo
Graphical abstract: Highlights: Long degradation kinetics could represent a limitation to hydrogel clinical application; Generally in biomaterials science the use of degradable cross-linkers is the answer; Here we used a polymer (hyaluronic acid) as degradable cross-links; The main advantage is that it can tune physico-chemical properties; Following this approach the formulation possibilities increases. Abstract: In the last decades hydrogels have demonstrated to be promising in multiple uses in medicine as controlled drug delivery systems and scaffolds for tissue engineering. In this fields a careful material design is crucial to achieve suitable and desired properties. In the last ten years we developed agarose-carbomer based hydrogels that exhibited good performances to repair damaged tissue working as cell carrier and sustaining the release of drugs. However the too long degradation kinetics associated to this formulation could represent an hindrance to tissue regrowth and so a limitation to its clinical application. In order to tune matrix degradability we modified the 3D network of agarose-carbomer hydrogels with hyaluronic acid chains that can work as degradable cross-links. The main advantages in using a polymer instead of small degradable cross-linkers reside in the possibility to take part to the entire network with the consequent possibility to tune so physico-chemical properties.